Some recommendations for the optimization of building of titles - Suvorova, S. A.; Суворова, Світлана Анатоліївна (My University, 2016)
Стаття присвячена дослідженню заголовків наукових робіт, а також аналізу та наданню деяких рекомендацій для оптимізації побудови цих заголовків з огляду на частоту їх використання.

The article is devoted to the study of titles of the scientific papers, as well as analysis and providing of some recommendations for the optimization of building these titles in accordance with the frequency of their use.
Suvorova S. A. Some recommendations for the optimization of building of titles / S. A. Suvorova // Одеський лінгвістичний вісник. - 2016. - Вип. 8. - С. 87-89.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; заголовок; фонові знання; статті; наукова комунікація; текст; механізм; контекст; title; background knowledge; article; scientific communication; text; mechanism; context